(untitled) (Interdisciplinary Studies Journal, 2025)
This work aims to analyze the socio-historical construction process of the Quilombola Remnant Community Novo Horizonte – Rincão dos Caixões based on Axel Honneth’s theory of recognition. The study is characterized as qualitative, descriptive, and exploratory. For this study, a segment of the project "Traditions and Memories: the symbolisms that reveal identity, ancestry, and the possibility of sustainable development in a Quilombola Community" from the Graduate Program in Sociocultural Practices and Social Development at the University of Cruz Alta - UNICRUZ was used, with support from Emater and Cáritas. The results were titled "Axel Honneth’s Theory of Recognition" and "The Socio-Historical Construction of the Quilombola Community Novo Horizonte - Rincão dos Caixões." The process of struggle and recognition of the Quilombola community continues to evolve and demands awareness regarding the rights of its members. Thus, the socio-historical construction of the Quilombola community reinforces the relevant role these spaces play in the Brazilian historical context as a mark of resistance against the oppression imposed by the slave regime and remains significant in preserving Afro-Brazilian traditions and cultures.